A metabolomic analytical approach permits identification of urinary biomarkers for Plasmodium falciparum infection: a case–control study - Abdelrazig, Salah M.A.; Ortori, Catharine A.; Davey, Gail; Deressa, Wakgari; Mulleta, Dhaba; Barrett, David A.; Amberbir, Alemayehu; Fogarty, Andrew W. (BioMed Central, 2017)
BACKGROUND: Currently available diagnostic techniques of Plasmodium falciparum infection are not optimal for non-invasive, population-based screening for malaria. It was hypothesized that a mass spectrometry-based metabolomics approach could identify urinary biomarkers of falciparum malaria.